Investigation of nonlinear optical properties on structures of silver micro-flowers - Zakaria, Rozalina; Mezher, M.H.; Chong, W.Y. (Springer, 2016)
In this report, we investigated nonlinear optical properties of silver microstructures in flowers like shape (AgMFs). These structures have been fabricated on indium–tin–oxide substrate applying electrochemical deposition technique using three different time depositions of Ag (NH3)2OH to produce different sizes of Ag structures in micron scale size. The nonlinear optical property of the material was investigated by a Z-scan technique using femtosecond laser pulses at 800 nm. The AgMFs with higher Ag concentration show a greater enhancement in magnitude and sharpness of the plasmon resonance band. We found out that AgMFs exhibit highly enhanced surface plasmon resonance sensitivity than previous work reported using Ag nanoparticles (AgNPs) structures as comparison due to the arbitrarily structures of micro-like flowers. The Z-scan measurement using pulse laser showed that the nonlinear absorption of AgMFs is as high as 3.7 × 10−9 cm2 W−1 compared to AgNPs as ~2 × 108 cm2 W−1.